P14.99 Clinical and biologic features predictive of survival after relapse of childhood medulloblastoma. (6th September 2019) - Huybrechts, S; Chivet, A; Tauziede-Espariat, A; Rossoni, C; Indersie, E; Varlet, P; Puget, S; Abbas, R; Ayrault, O; Guerrini-Rousseau, L; Grill, J; Valteau-Couanet, D; et al.
Abstract: BACKGROUND: Salvage therapy for recurrent medulloblastoma (MB) is not standardized. Factors associated with survival after recurrence have not been reported. MATERIAL AND METHODS: Medical records were reviewed for 155 consecutive patients with newly diagnosed MB between 2007 and 2017, treated at Gustave Roussy and Hospital Necker. The following variables were collected for all patients: age at diagnosis, stage, histology (central review according to WHO 2016 classification), molecular subgrouping (DNA methylation), first-line treatment modalities, time to relapse, pattern of recurrence and current status. RESULTS: A disease recurrence was observed in 47 patients (30%) at a median time of 15 months (range, 1–88 months). The 1-year survival after recurrence was 44% (CI 95%, 29.6 to 58.8). The pattern of recurrence was local in 9 patients, metastatic in 21 and combined local and metastatic in 17 patients. The time to first recurrence, less or more than 12 months from diagnosis, was a predictor of post-recurrence overall survival (p < 0.0001) after adjustment for age, treatment, MYC amplification and molecular subgroups. Twenty-seven patients (57%) experiencing recurrent or progressive disease more than 12 months after diagnosis, had an estimated 1-year survival after recurrence of 100% (CI 95%, 100.0 to 100.0) vs 30% (CI 95%, 12.2 to 50.1) with an earlier recurrence. Early relapse was more frequent in children younger than 5 years of age at diagnosis (75% vs 37%, p =0.009), anaplastic/large cell MB (30% vs 3.7%, p=0.046) and Group 3 tumours (76.5% vs 20.8%, p=0.003). Other factors influencing post-relapse survival were metastatic disease and treatment modalities at diagnosis. Multivariable analyses will be presented. CONCLUSION: The overall prognosis after relapse remains poor. Time to relapse is a significant prognostic factor for postrelapse survival and may help in the design of clinical trials evaluating new agents.